Effectiveness of transdermal NSAID administration in analgesia for rib fracture patients: a comparative study with intravenous NSAID administration - Kottareddygari, Vikas Sankar; C. A., Shashirekha; Baig, Asadulla; N., Suryateja; P. N., Sreeramulu (International Surgery Journal, 2018)
Background: Simple rib fractures are the most common injuries sustained following blunt trauma chest, accounting for more than half of thoracic injuries from nonpenetrating trauma. Looking into new modalities of administration like transdermal patches helps reduce morbidity in such patients with minimal side effects. The objectives of this study were to assess the effectiveness of transdermal NSAID administration in analgesia for rib fracture patients and to compare the effectiveness with intravenous NSAID administration. Methods: A prospective study comprising of 50 rib fracture patients who presented to the Emergency Medicine Department at RL Jalappa Hospital and Research Centre, Tamaka, Kolar. Study group were administered transdermal NSAID and the control group were administered intravenous NSAID. Results: Of the 50 subjects studied, 9 were female and 41 were male. Group A in which transdermal NSAIDs were administered consisted of 2 females and 23 male subjects while Group B in which intravenous NSAIDs were administered consisted of 7 females and 18 male subjects. The comparison was made between the two groups. The study results showed that the analgesia effect with transdermal NSAID administration is slow in onset as evidenced by higher VAS readings on day 1 whereas it is comparable with analgesia effect of intravenous NSAID administration in the long run as evidenced by VAS readings on day 3. Conclusions: Transdermal NSAID administration is effective in analgesia for rib fracture cases. The analgesia effect with transdermal NSAID administration is slow in onset as evidenced by high VAS readings on day 1 whereas it is comparable with analgesia effect of intravenous NSAID administration in the long run as evidenced by VAS readings on day 3.